Karakteristik Kajian Islam Kontemporer: Dialektika Barat dan Timur - Amirudin Amirudin; Masayu Mashita Maisarah (Eduprof : Islamic Education Journal, 2020)
Islam is understood in multi-meaning, as a religious teaching and as a scientific field. This matter is still being debated by several groups, especially regarding the issue surrounding studying Islam in the West. The purpose of this paper is to examine the development of Islamic studies from time to time. The issue of using a normative and historical approach in Islamic studies has been widely discussed by experts, both from the West and the East. However, in its development, Islamic studies form a separate 'stronghold' with their respective identities in an effort to understand Islamic teachings, both as an 'observer' and as an 'actor' who has an element of partiality. By using a historical approach, this paper will prove the flexibility of Islamic studies, where each "camp" will have its own method and style in understanding Islamic teachings, both in its development in the East and West. The study of Islam will always be up to date because it attracts attention. This is of course not only among Muslims (insiders), but also among non-Muslims (outsiders) who study Islam from various perspectives. Abstrak Islam dipahami dengan multi-makna, sebagai ajaran keagamaan dan sebagai bidang keilmuan. Hal tersebut hingga kini masih diperdebatkan oleh beberapa kalangan, terutama menyangkut isu seputar mengkaji Islam di Barat. Tujuan tulisan ini ingin mengkaji perkembangan studi Islam dari masa ke masa. Isu penggunaan pendekatan normatif maupun historis dalam kajian Islam telah ramai diperbincangkan oleh para ahli, baik dari Barat maupun Timur. Namun dalam perkembangannya, studi Islam membentuk ‘kubu’ tersendiri dengan identitas masing-masing dalam upaya memahami ajaran Islam, baik sebagai ‘pengamat’ maupun sebagai ‘aktor’ yang memiliki unsur keberpihakan. Dengan menggunakan pendekatan historis, tulisan ini akan membuktikan fleksibilitas kajian Islam, di mana masing-masing ‘kubu’ akan memiliki metode dan corak tersendiri dalam memahami ajaran Islam, baik perkembangannya di Timur dan Barat. Kajian tentang ke-Islaman akan selalu aktual untuk diperbincangkan karena sangat menarik perhatian. Hal ini tentunya tidak hanya dikalangan muslim sendiri (insider), tetapi juga kalangan non-muslim (outsider) yang mempelajari agama Islam dari berbagai sudut pandang.